Nomination of two cassava varieties (UMUCASS 55-Renewed Hope and UMUCASS 56-BIGGIE) for processing and industry market segments for registration and release in Nigeria - Egesi, C.N; Okeakpu, F.; Njoku, D.; Jiwuba, L.; Kulakow, P.; Ekanem, U.O.; Mbanjo, E.G; Parkes, E.; Rabbi, I.Y. (2024)
Cassava (Manihot esculenta Crantz) is not only a staple food crop but has also become a major industrial and income-generating crop in sub-Saharan Africa (SSA). In Nigeria, a large portion of the population relies on cassava for both their livelihood and employment within the cassava value chain. With rapid industrial growth and innovation, the increasing demand for cassava as a raw material presents significant opportunities for improved livelihoods and income